2022
DOI: 10.1038/s41467-022-28180-4
|View full text |Cite
|
Sign up to set email alerts
|

General synthesis of ultrafine metal oxide/reduced graphene oxide nanocomposites for ultrahigh-flux nanofiltration membrane

Abstract: Graphene-based membranes have great potential to revolutionize nanofiltration technology, but achieving high solute rejections at high water flux remains extremely challenging. Herein, a family of ultrafine metal oxide/reduced graphene oxide (rGO) nanocomposites are synthesized through a heterogenous nucleation and diffusion-controlled growth process for dye nanofiltration. The synthesis is based on the utilization of oxygen functional groups on GO surface as preferential active sites for heterogeneous nucleat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 59 publications
2
78
0
Order By: Relevance
“…The incorporation of GO increased the FWHM of nanocomposites, indicating more oxygen containing groups inside. However, the FWHM decreased with the increase of GO wt% and also high DS of the carbazate groups for PVA-N-GO, attributed to more rGO existed inside the corresponding nanocomposites ( Rahoui et al, 2018 ; Zhang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
“…The incorporation of GO increased the FWHM of nanocomposites, indicating more oxygen containing groups inside. However, the FWHM decreased with the increase of GO wt% and also high DS of the carbazate groups for PVA-N-GO, attributed to more rGO existed inside the corresponding nanocomposites ( Rahoui et al, 2018 ; Zhang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
“…Pristine GO- or rGO-coated membranes have low flux due to short d -spacings of GO and rGO laminates (0.8 and 0.35 nm, respectively) . This dense membrane structure would greatly hinder water transport leading to extremely low water permeation due to strong capillary forces in the compact nanochannels . While dense graphene membranes are effective at rejecting OMPs, the extremely low water fluxes through these membranes limit their use for most applications requiring OMP removal.…”
Section: Nanocomposite Polymeric Membranes For Omp Removalmentioning
confidence: 99%
“…Widening the interlayer spacing has been used to modulate permeation in rGO films, and can comprise cationic crosslinking [103], carbon nanotube intercalation [104], polymer additives [105], etc. Zhang et al [106] demonstrated a versatile and facile method to synthesize ultrafine metal oxide/rGO nanocomposites through a heterogeneous nucleation and growth process for nanofiltration applications (Figure 7a). The uniform adhesion of these ultrafine metal oxide nanoparticles effectively suppressed the wrinkling and stacking of the resulting rGO sheets.…”
Section: Rgo Membranementioning
confidence: 99%